Computational Study of Traveling Wave Solutions of Isothermal Chemical Systems (Communications in Computational Physics, 2020)
This article studies propagating traveling waves in a class of reaction-diffusionsystems which model isothermal autocatalytic chemical reactions as well as microbialgrowth and competition in a flow reactor. In the context of isothermal autocatalyticsystems, two different cases will be studied. The first is autocatalytic chemical reactionof order m without decay. The second is chemical reaction of order m with a decay oforder n, where m and n are positive integers and m >n≥1. A typical system in autocatalysisis A+2B→3B and B→C involving two chemical species, a reactant A and anauto-catalyst B and C an inert chemical species.The numerical computation gives more accurate estimates on minimum speed oftraveling waves for autocatalytic reaction without decay, providing useful insight inthe study of stability of traveling waves.For autocatalytic reaction of order m=2 with linear decay n=1, which has a particularimportant role in chemical waves, it is shown numerically that there exist multipletraveling waves with 1, 2 and 3 peaks with certain choices of parameters.